Perlindungan Konsumen Terhadap Peredaran Handphone International Mobile Equipment Identity (IMEI) Ilegal Perspektif Sadd Al- Dzari’ah - Sonia Natasya Hasugian; Muhammad Ramadhan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Consumers are an important element in the economy through various factors such as buying and selling communication devices or often called cellphones. Mobile phones are something that must co-exist with humans nowadays, there are many different types of mobile phones offered with features that make their respective products superior. However, some people in Indonesia choose to buy imported mobile phones from abroad rather than buying mobile phones at official shops in Indonesia. Indonesia. Thus, consumers must receive legal protection if the cellphone they buy is a cellphone with an illegal name. And if it is related to sadd al-dzari'ah work that causes damage/loss to one of the parties, then this action is prohibited. This is what raises problems related to consumer protection regarding the circulation of cellphones with illegal titles which are currently widespread in Indonesian society. This research uses Normative Law research or legal research which views law as building a system of norms. The method used by the author is in the form of collecting sentences from scientific works, notebooks, approaches to legislation, relevant journals. The results of this research are to obtain rights and protection for consumers who have already purchased cellphones with illegal IMEIs in accordance with Indonesian law and also the sadd al-dzari'ah perspective.